2022
DOI: 10.1021/acssynbio.1c00593
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Analysis of Bacillus licheniformis for Improving Bacitracin Production

Abstract: This study aims to find the targets that may influence the production of bacitracin based on RNA sequencing in Bacillus licheniformis. Transcriptional profiling revealed that (i) the expression of the bacT gene, encoding a type II thioesterase (TEII bac ), was positively correlated with bacitracin production and (ii) the oxygen uptake exhibited significant influence on precursor synthesis. The verified experiments showed that the overexpression of TEII bac with an endogenous promoter increased the bacitracin A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…The bacitracin synthetase gene cluster comprises bacABC operon and type II thioesterase gene bacT , and the function of latter has not been well analyzed [ 15 ]. Recently, Wu et al demonstrated that bacT expression positively correlated with bacitracin synthesis according to transcriptomic analysis, and overexpression of bacT increased bacitracin A yield by 37.50% [ 16 ]. The bacitracin synthetase gene cluster bacABC is located downstream of bacT , among which, BacA (598 kDa) activates and polymerizes four amino acids (L-Ile, L-Leu, L-Cys, and D-Glu) in the tail of bacitracin, BacB (291 kDa) and BacC (723 kDa) are responsible for the activation and amidation of remaining seven amino acids [ 17 , 18 ] ( Fig.…”
Section: Regulation and Associated Mechanisms Of Bacitracin Biosynthe...mentioning
confidence: 99%
See 1 more Smart Citation
“…The bacitracin synthetase gene cluster comprises bacABC operon and type II thioesterase gene bacT , and the function of latter has not been well analyzed [ 15 ]. Recently, Wu et al demonstrated that bacT expression positively correlated with bacitracin synthesis according to transcriptomic analysis, and overexpression of bacT increased bacitracin A yield by 37.50% [ 16 ]. The bacitracin synthetase gene cluster bacABC is located downstream of bacT , among which, BacA (598 kDa) activates and polymerizes four amino acids (L-Ile, L-Leu, L-Cys, and D-Glu) in the tail of bacitracin, BacB (291 kDa) and BacC (723 kDa) are responsible for the activation and amidation of remaining seven amino acids [ 17 , 18 ] ( Fig.…”
Section: Regulation and Associated Mechanisms Of Bacitracin Biosynthe...mentioning
confidence: 99%
“…Moreover, increasing the dissolved oxygen content augments ATP supply and facilitates antibiotic production [ 69 ]. In particular, Wu et al have increased the availability of oxygen via heterologous expression of Vitreoscilla hemoglobin VHb, thereby increasing bacitracin A titer by 126.67% under the oxygen-restricted conditions [ 16 ].…”
Section: Metabolic Engineering For Efficient Production Of Bacitracinmentioning
confidence: 99%
“…Transcriptomic technologies have opened new avenues for guiding the construction of high-production strains by providing a deeper understanding of the genetic background of microorganisms, and allow rapid selection of effective metabolic engineering targets. Bacitracin yield was significantly increased by rational engineering of B. licheniformis on the basis of transcriptome data, demonstrating that TEII bac (encoding type II thioesterase) and oxygen supply are critical for bacitracin production [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Researches on the physiology of B. licheniformis date back to the 1970s, and after half a century of intensive development, the achievements have been impressive. Nowadays, biotechnology has undergone rapid iterations, and multiomics information of B. licheniformis, including genome, transcriptome [2] and proteome [3], has also been accurately presented for better exploitation with the help of advanced bioinformatics techniques. The concept of biomanufacturing has been developed in recent years [4], with this background, the use of B. licheniformis as expression system would be an upgraded roadmap for its application.…”
Section: Introductionmentioning
confidence: 99%